2004
DOI: 10.1051/0004-6361:20034264
|View full text |Cite
|
Sign up to set email alerts
|

Cool carbon stars in the halo: A new survey based on 2MASS

Abstract: Abstract. We present the first results of a new survey for finding cool N-type carbon (C) stars in the halo of the Galaxy. Candidates were first selected in the 2MASS Second Incremental Release database with JHK s colours typical of red AGB C stars and K s < 13, and subsequently checked through medium resolution slit spectroscopy. We discovered 27 new C stars plus one known previously and two similar objects in the Fornax and Sculptor dwarf galaxies. We determine and discuss the properties of our sample, inclu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 43 publications
2
78
0
Order By: Relevance
“…Zero point adjustment Mauron et al (2004) have observed a ∼±10 km s −1 dispersion in the velocity residuals of several APM stars they used as velocity templates. Such zero point uncertainty suggest that the Totten & Irwin (1998) velocity determination of C stars may have errors larger than the quoted values.…”
Section: Velocity Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Zero point adjustment Mauron et al (2004) have observed a ∼±10 km s −1 dispersion in the velocity residuals of several APM stars they used as velocity templates. Such zero point uncertainty suggest that the Totten & Irwin (1998) velocity determination of C stars may have errors larger than the quoted values.…”
Section: Velocity Determinationmentioning
confidence: 99%
“…Weinberg & Nikolaev (2001) have shown that N-type C stars can be used, under certain colour restrictions, as reliable standard candles showing a small dispersion in M K . More recently Mauron et al (2004) followed a similar method to determine the distances for several halo C stars. This approach is preferable to the P−L relation which requires the C star to be a Mira of known period.…”
Section: Introductionmentioning
confidence: 99%
“…There are no such objects with K > 11 because AGB stars as faint as this in K (and consequently very distant in the halo) are very rare, and are only found with specific methods (see, e.g. Mauron et al 2004Mauron et al , 2005. We suggest that HES objects with J − K < 1 are red giant branch objects, or for a small fraction, dwarfs (see below).…”
Section: Discussionmentioning
confidence: 87%
“…This is obviously due to its blue−visible spectral range. For example, HES missed 11 C stars listed in Mauron et al (2004Mauron et al ( , 2005, although these objects satisfy R < 16, b < −30 • and δ < +2 • . The reason is that their B − R colour is too large and the signal at blue wavelengths is too faint.…”
Section: Mass Photometrymentioning
confidence: 99%
See 1 more Smart Citation